Preparation method of C60 electron transport layer and perovskite solar cell

By using a self-assembled template layer to encapsulate carbon 60 in perovskite solar cells, the problem of difficult to control the thickness and uniformity of carbon 60 film layer is solved, the performance and stability of the solar cell are improved, and the production cost is reduced.

CN119421627APending Publication Date: 2025-02-11JIANGSU MICROVIA NANO EQUIP TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411479249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to prepare a carbon 60 film layer with good thickness uniformity on a large-sized substrate, resulting in problems with electron transport efficiency and charge recombination, affecting the efficiency and stability of perovskite solar cells.

Method used

Accurate control of the thickness and uniformity of the carbon 60 film layer is achieved by forming a supramolecular polymer template layer of hydrophobic pore using self-assembleable monomer compounds.

Benefits of technology

The uniform thickness and distribution of the carbon 60 film layer is achieved, the electron transmission performance of perovskite solar cells is improved, the service life of the battery is extended, and energy consumption and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097038050000021
    Figure BDA0005097038050000021
  • Figure BDA0005097038050000022
    Figure BDA0005097038050000022
  • Figure BDA0005097038050000031
    Figure BDA0005097038050000031
Patent Text Reader

Abstract

The invention provides a preparation method of a C60 electron transport layer and a perovskite solar cell, and the preparation method comprises the following steps: S1, dispersing a self-assembled monomer compound in a solvent, and standing to obtain a supramolecular polymer template solution with hydrophobic pore channels; carrying out negative ion treatment on the substrate to enable the surface of the substrate to have negative electricity; s2, coating the substrate with negative electricity on the surface with the supramolecular polymer template solution, and self-assembling to form a template layer; and S3, coating the substrate on which the template layer is formed with a C60 dispersion liquid, and then removing the template layer to obtain the C60 film. The prepared C60 film can be applied to an electron transport layer of a perovskite solar cell, accurate control over the thickness and uniformity of the film layer is achieved, and the transport performance of the perovskite solar cell is improved. The method does not need to use evaporation equipment, can reduce energy consumption and cost, and is simple in process, convenient to operate and suitable for industrial large-scale popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photovoltaics, and in particular relates to a method for preparing a carbon 60 electron transport layer and a perovskite solar cell. Background Art

[0002] Perovskite solar cells (abbreviated as perovskite cells) are photovoltaic devices based on perovskite materials. Their basic structure is usually: substrate material / conductive glass (substrate glass coated with an oxide layer) / electron transport layer (titanium dioxide) / perovskite absorption layer (hole transport layer) / metal cathode. Perovskite solar cells have the advantages of high efficiency and low cost, and have attracted much attention in the photovoltaic field in recent years.

[0003] In perovskite solar cells, carbon 60 is often used as an electron transport material because of its excellent properties such as providing high electron mobility, helping electrons to be quickly transported within the perovskite material layer, thereby improving the efficiency of the solar cell; helping to transfer electrons between the perovskite layer and the electrode, enhancing the conductivity of electrons, thereby improving the performance of the battery; and improving the stability of perovskite solar cells, slowing down the degradation of the perovskite layer, and extending the service life of the battery.

[0004] At present, how to prepare a carbon 60 electron transport layer with uniform distribution and precisely controllable thickness is a key problem to be solved by various technologies. Nowadays, the common methods for preparing carbon 60 electron transport layers include spin coating method, vacuum evaporation method, etc. Among them, the spin coating method is referred to as spin coating method, which mainly forms a film layer by high-speed rotation to evaporate the solvent of the spin coating liquid on the substrate; although it is simple and easy to operate, it is difficult to prepare a carbon 60 film layer with good thickness uniformity on a large-size substrate. The vacuum evaporation method is to heat the material in a vacuum environment and form a coating on the surface of the substrate by evaporation or sublimation. It is also difficult to achieve uniform distribution of the carbon 60 layer on a nanometer thickness scale, which leads to problems such as electron transmission efficiency and charge recombination, and ultimately affects the efficiency and stability of perovskite solar cells. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing a carbon 60 electron transport layer and a perovskite solar cell. The present invention can achieve good control of the thickness and uniformity of the carbon 60 film layer, which can be applied to the electron transport layer of the perovskite solar cell, thereby improving the transmission performance of the perovskite solar cell, etc.

[0006] The present invention provides a method for preparing a carbon 60 film, comprising the following steps:

[0007] S1, dispersing a self-assembling monomer compound in a solvent and allowing the solvent to stand to obtain a supramolecular polymer template solution having hydrophobic channels;

[0008] The substrate is treated with negative ions using oxygen plasma to make the surface of the substrate negatively charged;

[0009] S2, coating the supramolecular polymer template solution on the substrate with negative charge on the surface, and self-assembling to form a template layer;

[0010] S3, coating a carbon 60 dispersion on the substrate on which the template layer is formed, and then optionally removing the template layer to obtain a carbon 60 film.

[0011] In an embodiment of the present invention, in step S1, the self-assembling monomer compound has a structure of Formula 1, wherein R1 is a methoxy group, a formaldehyde group, an amino group, a nitrile group or a nitro group, R2 is a single-arm or multi-arm polyethylene glycol chain; x is an integer between 2 and 4;

[0012]

[0013] In Formula 1, R2 is preferably any of the following structures:

[0014]

[0015] Among them, y1 is an integer between 8 and 14, and y2 is an integer between 4 and 6.

[0016] In an embodiment of the present invention, in step S1, the monomer compound is generated by reacting a polyethylene glycol pyridine compound shown in formula 2 and a biphenyl derivative shown in formula 3;

[0017]

[0018] In an embodiment of the present invention, in the step S1, the concentration of the monomer compound in the solvent is 0.1 to 10 wt %, the solvent is methanol, and the monomer compound is dispersed in a water bath by ultrasonication for 1 to 60 min;

[0019] And / or, in the step S2, the supramolecular polymer template solution is excessively coated on the substrate with a negatively charged surface, and waits for self-assembly, and after standing for 1 to 60 minutes, self-assembles to form a template layer.

[0020] In an embodiment of the present invention, the gases used for the oxygen plasma negative ion treatment are argon and oxygen; the argon-oxygen ratio may be 1 to 0.2:1;

[0021] And / or, the discharge power of the oxygen plasma for negative ion treatment is 50 to 500 W;

[0022] and / or, the oxygen plasma negative ion treatment time is 0.5 to 10 minutes,

[0023] In an embodiment of the present invention, in step S3, the concentration of the carbon 60 dispersion is 0.01-0.3 wt %, and is excessively coated on the substrate forming the template layer, and after the carbon 60 is deposited in the hydrophobic pores of the template layer, the excess carbon 60 dispersion is removed;

[0024] And / or, the solvent in the carbon 60 dispersion is toluene.

[0025] In an embodiment of the present invention, in step S3, the removal of the template layer is achieved by dissolving with alcohol, and the alcohol is preferably ethanol and / or propanol.

[0026] In an embodiment of the present invention, the thickness of the carbon 60 film is within 4 nm.

[0027] The present invention provides an electron transport layer, which is a carbon 60 film obtained by the preparation method described above.

[0028] The present invention provides a perovskite solar cell, comprising the electron transport layer.

[0029] Compared with the prior art, the embodiment of the present invention uses a self-assembled compound as a monomer, forms a template layer by self-assembly, and uses the template formed by self-assembly to prepare a carbon 60 electron transport layer, and closely distributes the annular self-assembly template with a hydrophobic cavity on a negatively charged substrate, and realizes the uniform encapsulation of carbon 60 in the nanopores of the template through hydrophobic interaction, thereby realizing the precise control of the thickness of the carbon 60 electron transport layer. Finally, the present invention utilizes the selective removal of the template layer so that the carbon 60 layer with a strictly distributed thickness is distributed on the surface of the substrate. The carbon 60 film prepared by this method can be applied to the electron transport layer of a perovskite solar cell. When applied to the electron transport layer of a perovskite solar cell, carbon 60 is easy to agglomerate when the thickness of the electron transport layer is thin. At this time, the template layer can be used to capture, fix and evenly disperse carbon 60. Therefore, after achieving uniform dispersion of carbon 60 on the template, the template layer is not removed, and the film thickness and uniformity can be precisely controlled to prevent carbon 60 from agglomerating, and improve the transmission performance of perovskite solar cells. The present invention does not require the use of evaporation equipment, can reduce energy consumption, reduce costs, and has a simple process and convenient operation, and is suitable for industrial-scale promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the process of applying C60 on the template layer in an embodiment of the present invention;

[0031] Figure 2 The following is a synthetic route diagram of monomer compounds in some embodiments of the present invention. DETAILED DESCRIPTION

[0032] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments.

[0033] The present invention provides a method for preparing a carbon 60 film, comprising the following steps:

[0034] S1, dispersing a self-assembling monomer compound in a solvent and allowing the solvent to stand to obtain a supramolecular polymer template solution having hydrophobic channels;

[0035] The substrate is treated with negative ions using oxygen plasma to make the surface of the substrate negatively charged;

[0036] S2, coating the supramolecular polymer template solution on the substrate with negative charge on the surface, and self-assembling to form a template layer;

[0037] S3, coating a carbon 60 aqueous dispersion on the substrate on which the template layer is formed, and then optionally removing the template layer to obtain a carbon 60 film.

[0038] The present invention can achieve good control of the thickness and uniformity of the carbon 60 film layer, and can be applied to the electron transport layer of the perovskite solar cell, thereby improving the transport performance of the perovskite solar cell, etc.

[0039] See also Figure 1 The method of the embodiment of the present invention mainly uses a self-assembled template to prepare a carbon 60 electron transport layer for a perovskite solar cell, which first forms a self-assembled template layer (such as Figure 1 The array structure template layer shown in green in the middle) is then applied with carbon 60 (C60, such as Figure 1 The C60 is uniformly encapsulated in the template layer (shown in blue in the middle), thereby forming a C60 film layer.

[0040] In step S1 of the embodiment of the present invention, the compound shown in formula 1 is used as a monomer compound of the self-assembly template layer, and the monomer compound has a hydrophilic polyethylene glycol segment and a hydrophobic biphenyl segment. In the preferred general structure of formula 1, x=2-4, specifically 2, 3 or 4; R1 is connected to one end of the biphenyl structure, and the other end is a pyridine group. R1 can be different organic functional groups, such as methoxy (-OCH3), amino (-NH2), formaldehyde (-CHO), nitrile (-CN), nitro (-NO2), etc., preferably an electron-withdrawing group, such as aldehyde (-CHO) and nitrile (-CN);

[0041]

[0042] In Formula 1, R2 is a single-arm or multi-arm hydrophilic polyethylene glycol chain, which can be a straight chain (single-arm, y1=8-14, specifically 9, 10, 11, 12, 13, 14), a double-branched chain (double-arm) or a quadruple-branched chain (quadruple-arm, y2=4-6, specifically 4, 5, 6), etc., specifically any of the following structures, "*" is a connecting bond;

[0043]

[0044] Some embodiments of the present invention take the monomer compound of double-branched polyethylene glycol chain as an example, and its synthesis route is shown in Figure 2 First, 2,6-dibromopyridinyl-4-ol is refluxed with the compound TsO-R2 (TsO is toluenesulfonyl), and this reaction can be achieved in the presence of potassium carbonate and the like, with acetonitrile as a solvent; the obtained compound containing a polyethylene glycol chain, 4-(trimethylsilyl)phenylboronic acid and tetrakis(triphenylphosphine)palladium are refluxed under a protective atmosphere, and then iodine monochloride is added to react to obtain a polyethylene glycol pyridine compound shown in formula 2; finally, it and the biphenyl derivative shown in formula 3 can be dissolved in toluene, ethanol and sodium carbonate, and then tetrakis(triphenylphosphine)palladium (which is a catalyst and can also replace other substances) is added to the mixture, and refluxed and stirred overnight under a protective atmosphere, and purified to obtain a white solid, which is the target product.

[0045]

[0046] In the above embodiment, the name of the biphenyl derivative shown in Formula 3 is 4,4,5,5-Tetramethyl-2-(4'-nitro-[1,1'-biphenyl]-4-yl)-1,3,2-dioxaborolane, Chinese name: 4,4,5,5-tetramethyl-2-(4'-nitro-[1,1'-biphenyl]-4-yl)-1,3,2-dioxaborolane; all raw materials are commercially available, and the reaction conditions are not particularly limited. In addition, other monomer compounds can be synthesized by similar routes.

[0047] In step S1 of the embodiment of the present invention, the monomer compound of formula 1 is preferably configured into a 0.1wt% to 10wt% methanol solution, and its concentration is more preferably 0.1 to 1wt% or 0.1 to 0.8wt%, so that the monomer compound can be in a uniformly dispersed state. In addition, ultrasound can be performed for 10 to 60 minutes or 10 to 40 minutes, and further for 15 to 30 minutes, preferably in an ice water bath, so that it has enough time and temperature to be completely dissolved and dispersed.

[0048] In the embodiment of the present invention, the methanol solution of the dispersed monomer compound formula 1 can be placed in a dark place at room temperature overnight to form a self-assembled and good template solution; the room temperature is generally 10-30°C, and the time is at least 12 hours. In the embodiment of the present invention, since the monomer compound formula 1 has a hydrophilic polyethylene glycol segment and a hydrophobic biphenyl segment connected thereto, it spontaneously forms a supramolecular polymer in a methanol solution under the action of hydrophilic and hydrophobic forces, and at the same time, due to the special geometric configuration of the biphenyls, it forms a directional self-assembled template solution with hydrophobic channels, that is, a supramolecular polymer template solution with hydrophobic channels. The monomer compound shown in Formula 1 is preferred in the present invention, because its specific polar groups, benzene rings and electronic distribution structures make the dispersibility and hydrophilicity moderate, which is conducive to the formation of a template with better channels and scales.

[0049] Moreover, in step S1 of the embodiment of the present invention, the substrate is preferably cleaned with acetone and water in sequence to ensure that the substrate is clean and free of oil, etc., and the instrument is also cleaned with plasma. After that, the embodiment of the present invention uses oxygen plasma to treat the cleaned substrate. During the discharge process, oxygen negative ions will bombard the substrate and make the surface of the substrate negatively charged, thereby realizing negative ion treatment of the substrate surface (which may be referred to as plasma surface treatment or plasma negative ion treatment, etc.), which is convenient for subsequent film formation. The embodiment of the present invention is also not limited to the material, size and characteristics of the substrate, and can be a flexible substrate such as a fiber fabric, a non-woven fabric, a thin film layer, or a rigid substrate such as a metal, glass, a ceramic semiconductor, a mineral, etc. When applied to the electron transport layer of a perovskite battery, when the electron transport layer is deposited on the perovskite layer, there is no need to perform a cleaning process. After the perovskite layer is prepared, oxygen plasma negative ion treatment can be directly performed. In order to reduce the impact on the perovskite layer, a lower oxygen plasma treatment power and less processing time are used.

[0050] The principle of plasma treatment technology is to use plasma formed by discharge or chemically active substances activated by plasma to react chemically with the surface of the material. In some embodiments of the present invention, the gas for plasma surface treatment is argon and / or oxygen. Specifically, the argon-oxygen ratio (flow ratio) of the plasma surface treatment may be 1 to 0.2:1; and / or, the discharge power of the plasma surface treatment is 50 to 500W; and / or, the time of the plasma surface treatment is 0.5 to 10 minutes, which fully makes the substrate negatively charged. After the surface of the substrate is negatively charged, there is an electrostatic interaction between it and the assembly of monomer compound formula 1. Due to the electrostatic effect, the supramolecular polymer will self-assemble on the surface of the substrate in the form of a two-dimensional monolayer, that is, forming a template layer. Therefore, it is necessary to first treat the substrate with negative ions of plasma, specifically by surface treatment with oxygen plasma, so that the surface of the substrate is negatively charged.

[0051] Then, in step S2 of the embodiment of the present invention, the self-assembly template solution described in the above step is dripped excessively on the substrate with negative charge on the surface, and waits for self-assembly. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution will be spread two-dimensionally on the substrate surface, and the spread is uniform. After 5 to 30 minutes of placement, the effect of the assembly on the substrate surface is close to saturation (preferably placed at room temperature for 6 to 20 minutes, 8 to 15 minutes, etc.), and the excess solution on the substrate can be blown away with a nitrogen gun, retaining the assembly adsorbed on the substrate to form a tightly distributed honeycomb structure, that is, forming a template layer.

[0052] In step S3 of the embodiment of the present invention, the carbon 60 dispersion can be dripped onto the substrate having the self-assembly template in the same manner, and the carbon 60 is gradually deposited into the hydrophobic channels of the template; it can then be blown dry with nitrogen (other inert gases can also be used to remove excess dispersion). Since the assembly has hydrophobic channels, the carbon 60 in the dispersion can be quickly captured inside the channels through hydrophobic interactions. At this time, the carbon 60 dispersion applied is relatively excessive relative to the template channels, and the excess carbon 60 will be removed together with the dispersion on the surface due to nitrogen blowing.

[0053] In a specific embodiment of the present invention, the carbon 60 dispersion is obtained by dispersing carbon 60 in a solvent, and the solvent is preferably toluene, and its concentration is preferably 0.01-0.3wt%, more preferably 0.03-0.1wt%, so as to form a uniform dispersion. The carbon 60 molecule is a molecule composed of 60 carbon atoms. The molecular structure of C60 is shaped like a football, so it is also called footballene; it is generally insoluble in strong polar solvents such as water, and has a certain solubility in non-polar solvents such as n-hexane, benzene, carbon disulfide, and carbon tetrachloride. The above-mentioned dropwise addition method can also be replaced by other coating operations so that the solution covers the surface of the substrate.

[0054] After drying the dispersion, in step S3 of the embodiment of the present invention, the template layer can be optionally removed to obtain a separate carbon 60 film layer with uniform thickness. It can be understood that the film layer only contains carbon 60 molecules; it can also be based on the need not to remove the template to obtain a composite film layer having a template layer and carbon 60. It can be understood that the film layer includes a template layer with hydrophobic channels and carbon 60 molecules in the hydrophobic channels. Whether to perform the template removal process can be selected according to the needs of the actual application. However, when the template removal process is required, alcohol, preferably ethanol and / or propanol, more preferably ethanol, is used, which is a good solvent for the assembly but a poor solvent for carbon 60. It is preferred to apply ethanol to dissolve and remove the template layer on the surface of the substrate. After the template layer is removed, a carbon 60 thin film layer is obtained, and the thickness of the template layer is the template thickness of the self-assembled 2D supramolecular polymer. Thus, carbon 60 forms a uniform thin film layer with a thickness of less than 4nm (such as 1 to 3nm, about 2nm).

[0055] The embodiment of the present invention provides an electron transport layer, which is a carbon 60 film obtained by the preparation method described above. As mentioned above, when preparing the carbon 60 film, the template removal step is not performed to improve the role of the template in grasping, fixing and uniformly dispersing the carbon 60 layer, which can achieve precise control of the film thickness and uniformity, prevent carbon 60 from agglomerating, and improve the transmission performance of the perovskite solar cell. The embodiment of the present invention also provides a perovskite solar cell, including the electron transport layer described above.

[0056] The method for preparing the carbon 60 film described in the embodiment of the present invention is a method for preparing the electron transport layer of a perovskite solar cell. The carbon 60 film as the electron transport layer can be directly based on the perovskite solar cell component (for the perovskite layer, in order to reduce the damage to the film layer caused by plasma treatment, the power of the negative ion treatment of the perovskite layer can be reduced to a lower level, such as 50W-70W and 0.5-1min for treatment time). The carbon 60 film layer can also be prepared and then transferred to the perovskite solar cell structure. The embodiment of the present invention has no special restrictions on other components of the perovskite solar cell, which are all perovskite cell components commonly used in the art, such as substrate glass coated with an oxide layer.

[0057] The embodiment of the present invention adopts a porous template formed by self-assembly to prepare a carbon 60 electron transport layer, which can achieve precise control and distribution of the thickness of the carbon 60 film layer at a scale of about 2 nanometers, which is beneficial to improving the transmission performance of the perovskite solar cell. In addition, under the premise of ensuring the uniform thickness of the carbon 60 electron transport layer of the perovskite cell, the present invention no longer requires the use of evaporation equipment, reduces energy consumption and cost, and has a simple process and convenient operation, and has a wide range of application prospects.

[0058] In order to further understand the present invention, the present invention is described in detail below in conjunction with the examples, and the protection scope of the present invention is not limited by the following examples. In the examples, all raw reagents and materials are commercially available, and the experimental methods without specifying specific experimental conditions are conventional methods and conditions well known in the art.

[0059] Example 1

[0060] (1) Figure 2 As shown, the synthesis of the monomer compound of formula 1 is as follows:

[0061] 1 g (4.0 mmol) of 2,6-dibromopyridinyl-4-ol, 2.80 g (4.0 mmol) of compound TsO-R2 and 4.40 g (28.0 mmol) of potassium carbonate were dissolved in 1000 mL of anhydrous acetonitrile, and the mixture was refluxed overnight and then cooled to room temperature. The reaction solvent was spin-dried, extracted with ethyl acetate and water, and the organic phase was dried over anhydrous magnesium sulfate. The crude product was purified by column chromatography to obtain a colorless oily liquid (yield: 4.3 g, 80%).

[0062] Take 1g (0.8mmol) of the obtained colorless oily liquid, dissolve it in dry tetrahydrofuran (10mL) and 2M sodium carbonate (10mL) with 385mg (2mmol) of 4-(trimethylsilane)phenylboronic acid, then add 45mg (0.038mmol) of tetrakis (triphenylphosphine) palladium to the mixture. The mixture was refluxed under argon protection for 12 hours. The crude product was purified by column chromatography to obtain a colorless oily liquid (yield: 760mg, 69%).

[0063] 760 mg (0.53 mmol) of the obtained colorless oily liquid (containing silicon compound) was dissolved in anhydrous dichloromethane, and 3.35 mL (2.95 mmol) of iodine monochloride solution (1M dichloromethane solution) was slowly added dropwise at -78°C. The mixture was stirred for 1 hour under nitrogen protection, and 3 mL of 1M sodium thiosulfate aqueous solution was added, and stirring was continued for 2 hours. The crude product was purified by column chromatography to obtain a colorless oily liquid (yield: 760 mg, 69%), which was recorded as compound formula 2.

[0064] 140 mg (0.09 mmol) of compound formula 2 and 121 mg (0.37 mmol) of 4,4,5,5-tetramethyl-2-(4'-nitro-[1,1'-biphenyl]-4-yl)-1,3,2-dioxaborane (recorded as compound formula 3) were dissolved in dry toluene (0.8 mL), ethanol (0.4 mL) and 2M sodium carbonate (0.2 mL), and then 5 mg (0.006 mmol) of tetrakis(triphenylphosphine)palladium was added to the mixture. The mixture was refluxed and stirred overnight under argon protective gas. The crude product was purified by column chromatography and then further purified by high performance liquid chromatography to obtain a white solid (yield: 80 mg, 50%), which was the target product.

[0065] Wherein, the structure of R2 in Formula 1 is as follows:

[0066]

[0067] (2) Preparation of C60 electron transport layer for perovskite solar cells:

[0068] Step 1: Prepare a 0.1 wt% methanol solution of the prepared monomer compound of formula 1, and perform ultrasonic treatment in an ice-water bath for 30 minutes to completely dissolve and disperse it.

[0069] Step 2: The dispersed methanol solution of the monomer compound of formula 1 is placed in a dark place at room temperature overnight to obtain a self-assembly template solution having hydrophobic channels.

[0070] Step 3: Treat the substrate with oxygen plasma at a power of 50 W for 1 min. During the discharge process, oxygen negative ions bombard the substrate, making the surface of the substrate negatively charged.

[0071] Step 4, drop the self-assembly template solution of step 2 onto the negatively charged substrate of step 3. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution is two-dimensionally evenly spread on the surface of the substrate. After 10 minutes, the effect of the assembly on the surface of the substrate is close to saturation. The excess solution on the substrate is blown away with a nitrogen gun, and the assembly adsorbed on the substrate is retained to form a template layer with a densely distributed honeycomb structure.

[0072] Step 5: In the same way, a carbon 60 dispersion (concentration of 0.1wt%, solvent of toluene) is dropped onto the substrate with the self-assembled template layer, and then blown dry with nitrogen to obtain a uniformly distributed carbon 60 film layer, the thickness of which is the template layer thickness of the self-assembled 2D supramolecular polymer, about 2 nanometers.

[0073] This embodiment is an inverse perovskite battery, and the specific preparation process is:

[0074] 1. Deposit FTO on a transparent substrate or glass to obtain a conductive glass layer;

[0075] 2. Depositing a nickel oxide layer;

[0076] 3. Deposition of perovskite layer;

[0077] 4. Prepare an electron transport layer, as described above;

[0078] 5. Deposit indium tin oxide layer and electrode layer.

[0079] This embodiment uses a self-assembled template to prepare a carbon 60 electron transport layer. The annular self-assembled template with a hydrophobic cavity is tightly distributed on a negatively charged substrate, and the carbon 60 is uniformly encapsulated in the nanopores of the template through hydrophobic interactions, thereby achieving precise control of the thickness of the carbon 60 electron transport layer, which is beneficial for application. When using this scheme to prepare the electron transport layer, in order to prevent damage to the perovskite layer by plasma treatment, a lower plasma treatment power and treatment time are selected, but the negative charge treatment of the substrate can also be achieved. While realizing the preparation of the inverse perovskite battery, the impact on the performance of the perovskite layer is not reduced.

[0080] The carbon 60 layer prepared by the above scheme has a more uniform thickness and can achieve the following effects:

[0081] (1) Improve the efficiency of electron transmission; the carbon 60 layer has a more uniform thickness, which can ensure that the electron transmission path in the carbon 60 layer is smoother and reduce the energy loss during electron transmission.

[0082] (2) Reduce charge recombination: The uniform distribution of the carbon 60 layer thickness can reduce the recombination rate of electrons and holes and improve the photoelectric conversion efficiency.

[0083] (3) Improve light absorption: The carbon 60 layer has a more uniform thickness, which can enhance light absorption, reduce reflection, and improve the overall performance of the battery.

[0084] (4) Enhance the structural stability of the battery; the carbon 60 layer has a more uniform thickness, which helps to improve the overall structural stability of the perovskite battery and extend the service life of the perovskite battery.

[0085] (5) Optimizing interface properties: A carbon 60 layer with uniform thickness can improve the quality of the contact interface between the carbon 60 layer and the perovskite layer, increase the filling factor, and thus improve the overall performance of the battery.

[0086] Example 2

[0087] Preparation of C60 electron transport layer for perovskite solar cells:

[0088] Step 1: Prepare a 1 wt % methanol solution of the prepared monomer compound of formula 1, and perform ultrasonic treatment in an ice-water bath for 40 min to completely dissolve and disperse the solution.

[0089] Step 2: Place the dispersed methanol solution of the monomer compound of formula 1 (prepared in Example 1) in a dark place at room temperature overnight to obtain a self-assembly template solution with hydrophobic channels.

[0090] Step 3, clean the substrate (conductive glass layer) with acetone / water, and use a plasma cleaning instrument; treat the cleaned substrate with oxygen plasma at a power of 300 W for 5 minutes. During the discharge process, oxygen negative ions bombard the substrate to make the substrate surface negatively charged.

[0091] Step 4, drop the self-assembly template solution of step 2 onto the negatively charged substrate of step 3. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution is two-dimensionally evenly spread on the surface of the substrate. After 5 minutes, the effect of the assembly on the surface of the substrate is close to saturation. The excess solution on the substrate is blown away with a nitrogen gun, and the assembly adsorbed on the substrate is retained to form a template layer with a densely distributed honeycomb structure.

[0092] Step 5: In the same way, a carbon 60 aqueous dispersion (concentration of 0.05wt%, solvent: toluene) is dropped onto the substrate with the self-assembled template layer, and then blown dry with nitrogen to obtain a uniformly distributed carbon 60 film layer, the thickness of which is the template layer thickness of the self-assembled 2D supramolecular polymer, about 2 nanometers.

[0093] This example is a formal perovskite battery, and its specific preparation process is as follows:

[0094] 1. Deposit FTO on a transparent substrate or glass to obtain a conductive glass layer;

[0095] 2. Prepare an electron transport layer, as described above;

[0096] 3. Deposition of perovskite layer;

[0097] 4. Depositing a nickel oxide layer;

[0098] 5. Deposit indium tin oxide layer and electrode layer.

[0099] This embodiment uses a self-assembled template to prepare a carbon 60 electron transport layer. The annular self-assembled template with hydrophobic cavities is closely distributed on a negatively charged substrate, and the carbon 60 is uniformly encapsulated in the nanopores of the template through hydrophobic interactions, thereby achieving precise control of the thickness of the carbon 60 electron transport layer, which is beneficial to application. When using this solution to prepare the electron transport layer, the electron transport layer is deposited on conductive glass. Because conductive glass has a strong surface strength, a larger plasma treatment power and treatment time can be selected without affecting the conductive glass substrate.

[0100] As described in Example 1, the carbon 60 electron transport layer prepared in this scheme is applied to perovskite cells, which can achieve beneficial effects such as improving electron transport efficiency, reducing charge recombination, improving light absorption, enhancing battery structure stability, and optimizing the interface characteristics between the electron transport layer and the perovskite layer.

[0101] Example 3

[0102] (1) The synthesis of the monomer compound of formula 1 was carried out according to the route of Example 1, except that a different compound TsO-R2 was used. R2 is shown below, and y1 is 8.

[0103]

[0104] (2) Preparation of carbon 60 layer:

[0105] Step 1: Prepare a 0.5 wt % methanol solution of the prepared monomer compound of formula 1, and perform ultrasonic treatment in an ice-water bath for 30 min to completely dissolve and disperse the solution.

[0106] Step 2: The dispersed methanol solution of the monomer compound of formula 1 is placed in a dark place at room temperature overnight to obtain a self-assembly template solution having hydrophobic channels.

[0107] Step 3, clean the glass substrate with acetone / water, and use a plasma cleaning instrument; treat the cleaned substrate with oxygen plasma at a power of 200 W for 5 minutes. During the discharge process, oxygen negative ions bombard the substrate to make the substrate surface negatively charged.

[0108] Step 4, drop the self-assembly template solution of step 2 onto the negatively charged substrate of step 3. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution is two-dimensionally evenly spread on the surface of the substrate. After 10 minutes, the effect of the assembly on the surface of the substrate is close to saturation. The excess solution on the substrate is blown away with a nitrogen gun, and the assembly adsorbed on the substrate is retained to form a template layer with a densely distributed honeycomb structure.

[0109] Step 5: In the same manner, a carbon 60 aqueous dispersion (concentration of 0.08 wt %, solvent: toluene) is dropped onto the substrate having the self-assembled template layer, and then blown dry with nitrogen.

[0110] Step 6: Use ethanol to remove the template layer on the surface of the substrate to obtain a uniformly distributed carbon 60 film layer. The thickness of the film layer is the thickness of the template layer of the self-assembled two-dimensional supramolecular polymer, which is about 2 nanometers.

[0111] This embodiment uses different monomer compound structures to prepare the template layer and prepares a carbon 60 layer, which can be applied to the electron transport layer of the perovskite battery.

[0112] Example 4

[0113] (1) The synthesis of the monomer compound of formula 1 was carried out according to the route of Example 1, except that a different compound TsO-R2 was used. R2 is shown below, and y2 is 5.

[0114]

[0115] (2) Preparation of carbon 60 layer:

[0116] Step 1: Prepare a 0.2 wt % methanol solution of the prepared monomer compound of formula 1, and perform ultrasonic treatment in an ice-water bath for 30 min to completely dissolve and disperse the solution.

[0117] Step 2: The dispersed methanol solution of the monomer compound of formula 1 is placed in a dark place at room temperature overnight to obtain a self-assembly template solution having hydrophobic channels.

[0118] Step 3, the PET substrate is cleaned with acetone / water, and a plasma cleaning instrument is used; the cleaned substrate is treated with oxygen plasma at a power of 350 W for 2 minutes. During the discharge process, oxygen negative ions bombard the substrate so that the substrate surface has negative charge.

[0119] Step 4, drop the self-assembly template solution of step 2 onto the negatively charged substrate of step 3. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution is two-dimensionally evenly spread on the surface of the substrate. After 10 minutes, the effect of the assembly on the surface of the substrate is close to saturation. The excess solution on the substrate is blown away with a nitrogen gun, and the assembly adsorbed on the substrate is retained to form a template layer with a densely distributed honeycomb structure.

[0120] Step 5: In the same manner, a carbon 60 aqueous dispersion (concentration of 0.1 wt %, solvent: toluene) is dropped onto the substrate having the self-assembled template layer, and then blown dry with nitrogen.

[0121] Step 6: Use ethanol to remove the template layer on the surface of the substrate to obtain a uniformly distributed carbon 60 film layer. The thickness of the film layer is the thickness of the template layer of the self-assembled two-dimensional supramolecular polymer, which is about 2 nanometers.

[0122] This embodiment uses different monomer compound structures to prepare the template layer and prepares a carbon 60 layer, which can be applied to the electron transport layer of the perovskite battery.

[0123] Example 5

[0124] (1) The synthesis of the monomer compound of formula 1 was carried out according to the route of Example 1, except that a different compound TsO-R2 was used. R2 is shown below, and y2 is 6.

[0125]

[0126] (2) Preparation of carbon 60 layer:

[0127] Step 1: Prepare a 1 wt % methanol solution of the prepared monomer compound of formula 1, and perform ultrasonic treatment in an ice-water bath for 30 min to completely dissolve and disperse the solution.

[0128] Step 2: The dispersed methanol solution of the monomer compound of formula 1 is placed in a dark place at room temperature overnight to obtain a self-assembly template solution having hydrophobic channels.

[0129] Step 3, the glass substrate is cleaned with acetone / water, and the instrument is cleaned with plasma; the cleaned substrate is treated with oxygen plasma at a power of 500 W for 7 minutes. During the discharge process, oxygen negative ions bombard the substrate so that the substrate surface has negative charge.

[0130] Step 4, drop the self-assembly template solution of step 2 onto the negatively charged substrate of step 3. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution is two-dimensionally evenly spread on the surface of the substrate. After 10 minutes, the effect of the assembly on the surface of the substrate is close to saturation. The excess solution on the substrate is blown away with a nitrogen gun, and the assembly adsorbed on the substrate is retained to form a template layer with a densely distributed honeycomb structure.

[0131] Step 5: In the same manner, a carbon 60 aqueous dispersion (concentration of 0.03 wt %, solvent: toluene) is dropped onto the substrate having the self-assembled template layer, and then blown dry with nitrogen.

[0132] Step 6: Use ethanol to remove the template layer on the surface of the substrate to obtain a uniformly distributed carbon 60 film layer. The thickness of the film layer is the thickness of the template layer of the self-assembled two-dimensional supramolecular polymer, which is about 2 nanometers.

[0133] This embodiment uses different monomer compound structures to prepare the template layer and prepares a carbon 60 layer, which can be applied to the electron transport layer of the perovskite battery.

[0134] Example 6

[0135] (1) The synthesis of the monomer compound of formula 1 was carried out according to the route of Example 1, except that a different compound TsO-R2 was used. R2 is shown below, and y2 is 4.

[0136]

[0137] (2) Preparation of carbon 60 layer:

[0138] Step 1: Prepare a 0.1 wt% methanol solution of the prepared monomer compound of formula 1, and perform ultrasonic treatment in an ice-water bath for 30 minutes to completely dissolve and disperse it.

[0139] Step 2: The dispersed methanol solution of the monomer compound of formula 1 is placed in a dark place at room temperature overnight to obtain a self-assembly template solution having hydrophobic channels.

[0140] Step 3, cleaning the glass substrate with acetone / water and using a plasma cleaning instrument; treating the cleaned substrate with oxygen plasma at a power of 400 W for 10 min. During the discharge process, oxygen negative ions bombard the substrate to make the substrate surface negatively charged.

[0141] Step 4, drop the self-assembly template solution of step 2 onto the negatively charged substrate of step 3. Due to the electrostatic effect, the supramolecular polymer in the self-assembly template solution is two-dimensionally evenly spread on the surface of the substrate. After 10 minutes, the effect of the assembly on the surface of the substrate is close to saturation. The excess solution on the substrate is blown away with a nitrogen gun, and the assembly adsorbed on the substrate is retained to form a template layer with a densely distributed honeycomb structure.

[0142] Step 5: In the same manner, a carbon 60 aqueous dispersion (concentration of 0.1 wt %, solvent: toluene) is dropped onto the substrate having the self-assembled template layer, and then blown dry with nitrogen.

[0143] Step 6: Use ethanol to remove the template layer on the surface of the substrate to obtain a uniformly distributed carbon 60 film layer. The thickness of the film layer is the thickness of the template layer of the self-assembled two-dimensional supramolecular polymer, which is about 2 nanometers.

[0144] This embodiment uses different monomer compound structures to prepare the template layer and prepares a carbon 60 layer, which can be applied to the electron transport layer of the perovskite battery.

[0145] It can be seen from the above embodiments that the embodiments of the present invention mainly use plasma to treat the substrate with negative ions, and then use the interaction between the supramolecular polymer of the monomer compound shown in Formula 1 and the negative charge to self-assemble on the surface of the substrate to form a two-dimensional porous template; and use the capture effect between the hydrophobic pores of the template and C60 to make C60 evenly spread in the pores, and then optionally remove the template to obtain a uniformly distributed C60 film with precisely controlled film thickness. The C60 film can be applied to the electron transport layer of perovskite solar cells. When applied to the electron transport layer of perovskite solar cells, carbon 60 is easy to agglomerate when the thickness of the electron transport layer is thin. At this time, the template layer can be used to capture, fix and evenly disperse carbon 60. Therefore, after achieving uniform dispersion of carbon 60 on the template, the template layer is not removed, and the film thickness and uniformity can be precisely controlled to prevent carbon 60 from agglomerating, thereby improving the transmission performance of the perovskite solar cell. The perovskite cell with a C60 electron transport layer of uniform thickness in the embodiment of the present invention has the following beneficial properties:

[0146] (1) Improve the efficiency of electron transmission; the carbon 60 layer has a more uniform thickness, which can ensure that the electron transmission path in the carbon 60 layer is smoother and reduce the energy loss during electron transmission.

[0147] (2) Reduce charge recombination: The uniform distribution of the carbon 60 layer thickness can reduce the recombination rate of electrons and holes and improve the photoelectric conversion efficiency.

[0148] (3) Improve light absorption: The carbon 60 layer has a more uniform thickness, which can enhance light absorption, reduce reflection, and improve the overall performance of the battery.

[0149] (4) Enhance the structural stability of the battery; the carbon 60 layer has a more uniform thickness, which helps to improve the overall structural stability of the solar cell and extend the service life of the perovskite cell.

[0150] (5) Optimizing interface properties: A carbon 60 layer with uniform thickness can improve the quality of the contact interface between the carbon 60 layer and the perovskite layer, increase the filling factor, and thus improve the overall performance of the battery.

[0151] The above examples are only used to illustrate the technical features and implementation process of the present invention, rather than to limit the technical solution of the present invention. It should be pointed out that for ordinary technicians in this field, the present invention can still be modified or replaced by equivalents, and modifications or replacements that do not deviate from the principles of the present invention are all covered by the protection of the present invention.

Claims

1. A method for preparing a carbon 60 film, characterized in that: The following steps are involved: S1, dispersing a self-assembling monomer compound in a solvent and allowing the solvent to stand to obtain a supramolecular polymer template solution having hydrophobic channels; The substrate is treated with negative ions using oxygen plasma to make the surface of the substrate negatively charged; S2, coating the supramolecular polymer template solution on the substrate with negative charge on the surface, and self-assembling to form a template layer; S3, coating a carbon 60 dispersion on the substrate on which the template layer is formed, and then optionally removing the template layer to obtain a carbon 60 film.

2. The preparation method according to claim 1, characterized in that: In step S1, the self-assembling monomer compound has a structure of formula 1, wherein R1 is a methoxy group, a formaldehyde group, an amino group, a nitrile group or a nitro group, R2 is a single-arm or multi-arm polyethylene glycol chain; x is an integer between 2 and 4; In Formula 1, R2 is preferably any of the following structures: Among them, y1 is an integer between 8 and 14, and y2 is an integer between 4 and 6.

3. The preparation method according to claim 2, characterized in that: In the step S1, the monomer compound is generated by reacting the polyethylene glycol pyridine compound shown in formula 2 and the biphenyl derivative shown in formula 3; 4. The preparation method according to any one of claims 1 to 3, characterized in that In the step S1, the concentration of the monomer compound in the solvent is 0.1 to 10 wt %, the solvent is methanol, and the monomer compound is dispersed in a water bath by ultrasonication for 1 to 60 min; And / or, in the step S2, the supramolecular polymer template solution is excessively coated on the substrate with a negatively charged surface, and waits for self-assembly, and after standing for 1 to 60 minutes, self-assembles to form a template layer.

5. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S1, the gases used for the oxygen plasma negative ion treatment are argon and oxygen; the argon-oxygen ratio may be 1 to 0.2:1; And / or, the discharge power of the oxygen plasma for negative ion treatment is 50 to 500 W; And / or, the oxygen plasma negative ion treatment time is 0.5 to 10 minutes.

6. The preparation method according to claim 5, characterized in that: In the step S3, the concentration of the carbon 60 dispersion is 0.01-0.3 wt %, and the dispersion is excessively coated on the substrate forming the template layer, and after the carbon 60 is deposited in the hydrophobic pores of the template layer, the excess carbon 60 dispersion is removed; And / or, the solvent in the carbon 60 dispersion is toluene.

7. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S3, the template layer is removed by dissolving with alcohol, and the alcohol is preferably ethanol and / or propanol.

8. The preparation method according to any one of claims 1 to 3, characterized in that: The thickness of the carbon 60 film is within 4 nm.

9. An electron transport layer, characterized in that It is a carbon 60 film obtained by the preparation method described in any one of claims 1 to 8.

10. A perovskite solar cell, characterized in that: Comprising the electron transport layer according to claim 9.